2022
DOI: 10.15294/jipk.v16i1.31361
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Belajar pada Mahasiswa Tadris Kimia Materi Biokimia di UIN SATU Tulungagung

Abstract: Biokimia adalah ilmu yang mengkaji mengenai substansi dan komposisi pada makhluk hidup. Mata kuliah Biokimia termasuk mata kuliah yang sulit untuk dipelajari oleh mahasiswa. Kesulitan belajar pada materi biokimia menyebabkan hasil belajar mahasiswa Tadris Kimia cenderung rendah. Tujuan penelitian ini adalah menganalisis kesulitan belajar mahasiswa tadris kimia di UIN SATU Tulungagung pada mata kuliah Biokimia. Metode penelitian menggunakan deskriptif analisis. Teknik analisis data dilakukan dengan tinjauan lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the table, before attending the lectures, most students have understood many chemistry concepts, both macroscopic concepts (i.e., types of general substances and specific materials) and sub-microscopic concepts that involve skills and reasoning (Astuti, 2020) as they studied chemistry in high school and everyday life. Even so, there were still difficulties in understanding related symbols, nomenclature, writing chemical for-mulas, and molecular shapes of organic and inorganic compounds since no deep discussion was undertaken about these concepts in high schools (Adlim et al, 2017;Priliyanti et al, 2021;Dewi, 2022). This study also showed a significant increase in student outcomes at the beginning of learning compared to the mid-semester on all the concepts studied.…”
Section: Resultsmentioning
confidence: 70%
“…In the table, before attending the lectures, most students have understood many chemistry concepts, both macroscopic concepts (i.e., types of general substances and specific materials) and sub-microscopic concepts that involve skills and reasoning (Astuti, 2020) as they studied chemistry in high school and everyday life. Even so, there were still difficulties in understanding related symbols, nomenclature, writing chemical for-mulas, and molecular shapes of organic and inorganic compounds since no deep discussion was undertaken about these concepts in high schools (Adlim et al, 2017;Priliyanti et al, 2021;Dewi, 2022). This study also showed a significant increase in student outcomes at the beginning of learning compared to the mid-semester on all the concepts studied.…”
Section: Resultsmentioning
confidence: 70%